Logistics policy analysis and network model simulation for cross-border transport in the Trans-Caspian transport corridor: Global intermodal logistics network simulation (GLINS) model - Daisuke Watanabe; Ryuichi Shibasaki; Hirofumi Arai (Asian Development Bank Institute (ADBI), 2021)
The countries in Central Asia (CA) are landlocked and without coastlines. Therefore, the Trans-Caspian Transport Corridor (TCTC) will play an important role in facilitating cross-border logistics in CA, particularly with land transport. To promote interregional collaborations between CA countries for managing these handicaps, the CA Regional Economic Cooperation (CAREC) Program was established through the leadership of the Asian Development Bank (ADB). This study focuses on the effectiveness of logistics policy and infrastructure development for cross-border transport along the TCTC using a simulation analysis based on a network equilibrium assignment model. The global logistics intermodal network simulation (GLINS) model, which the authors developed to cover intermodal freight transport networks (including roads, railways, ferries, and maritime shipping across the Eurasian continent) is used for policy simulation in the CA. In particular, the simulation incorporates the impact of the logistics policies related to cross-border transport in the TCTC, including the improvement of ferry services and rail networks along the corridor. The simulation results support the Kazakhstani approach, which emphasizes transit time reduction and transport tariffs while simultaneously enhancing cooperation within the Trans-Caspian International Transport Route Association.
Keywords: C63; R42; 330; logistics; network equilibrium model; Eurasian landbridge; Central Asia